Kepemimpinan Pendidikan Islam Perspektif Transformational Leadership - Edi Sugianto; Putri Nabila Rizki (Jurnal Tahdzibi: Manajemen Pendidikan Islam, 2026)
This study is motivated by the dominance of administrative leadership patterns in Islamic educational institutions that have not fully encouraged institutional transformation. This condition affects low levels of innovation, teacher motivation, and the overall quality of learning. The study aims to analyze Islamic educational leadership through the perspective of transformational leadership by examining the integration of Islamic values into leadership practices. This research employs a qualitative approach using library research, with data sources consisting of books, journal articles, and relevant scholarly documents. The research instrument is a data extraction form, while data collection is conducted through documentation and analyzed using thematic and content analysis. The subjects of the study are selected literature sources determined purposively based on relevance and credibility. The findings reveal that transformational leadership in Islamic education strengthens institutional vision, enhances intrinsic motivation, fosters innovation, and builds a value-based organizational culture grounded in trustworthiness, exemplary conduct, and consultation. This integration produces leadership that is not only managerially effective but also ethically and spiritually grounded. In conclusion, transformational leadership is relevant for developing Islamic educational leadership that is adaptive, inspirational, and value-oriented